Frequent productive cough: Symptom burden and future exacerbation risk among patients with asthma and/or COPD in the NOVELTY study. (August 2022) - Hughes, Rod; Rapsomaniki, Eleni; Janson, Christer; Keen, Christina; Make, Barry J.; Burgel, Pierre-Régis; Tomaszewski, Erin L.; Müllerová, Hana; Reddel, Helen K.; ,; Benhabib, Gabriel; Ruiz, Xavier Bocca; et al.
Abstract: Introduction: Persistent cough with sputum production is an important clinical trait in chronic obstructive pulmonary disease (COPD). We defined "frequent productive cough" based on 2 questions from the St George's Respiratory Questionnaire (SGRQ) and sought to determine its occurrence and associated outcomes in patients with physician-assigned asthma and/or COPD from the NOVELTY study. Methods: Frequent productive cough was defined as cough and sputum production most or several days/week for the past 3 months (scoring ≥3 for both SGRQ questions). Relationships with baseline disease characteristics and exacerbations over 12 months' follow-up were examined using logistic regression. Results: Baseline SGRQ data were available for 7125 patients, of whom 31.3% had frequent productive cough. It was more common in asthma+COPD (38.8%) and COPD (38.1%) than asthma (25.0%), increasing with physician-assessed severity, and in current versus former and never smokers. Patient-reported symptomatic worsening was more common in patients with versus without frequent productive cough. Reduced post-bronchodilator FEV1 (odds ratio [OR] per 10% decrement 1.14 [95% confidence interval 1.11–1.16]) and history of pollutant exposure at home/work (OR 1.50 [1.33–1.69]) were associated with frequent productive cough in all diagnoses. Patients with baseline frequent productive cough were more likely to have ≥1 exacerbation over the subsequent 12 months (OR 1.71 [1.52–1.93]), including exacerbations requiring hospital admission and those treated with oral corticosteroids. Conclusions: Frequent productive cough represents an important indicator of adverse clinical outcomes across asthma and/or COPD. Research into the underlying pathologic mechanisms is required to support targeted therapy development. Clinicaltrials.gov: NCT02760329. Highlights: Frequent productive cough was present across physician-assigned asthma and/or COPD. Prevalence of this clinical trait increased with higher physician-assessed severity. The trait was associated with reduced FEV1 and pollutant exposure in all diagnoses. Frequent productive cough was associated with higher risk of greater disease burden.